Impact of sports participation on components of metabolic syndrome in adolescents: ABCD growth study - Menezes, Veronica Alves de [UNESP]; Torres, Wesley [UNESP]; Mesquita, Eduardo Duarte de Lima [UNESP]; Chagas, Lucas Gabriel de Moraes [UNESP]; Morano, Ana Elisa von Ah [UNESP]; Urban, Jacqueline Bexiga [UNESP]; Avelar, Ademar; Christofaro, Diego Giuliano Destro [UNESP]; Fernandes, Romulo Araujo [UNESP] (De Gruyter, 2022)
Objectives This study aimed to analyze the impact of sports participation (12 months of practice) on the components of metabolic syndrome (MetS) in both sexes. Methods This is an observational longitudinal study, a part of which is entitled “Analysis of Behaviors of Children During Growth” (ABCD Growth Study), Presidente Prudente, São Paulo, Brazil. The sample was composed of 171 adolescents (112 boys and 59 girls), divided into non-sports and sports groups. High-density lipoprotein-cholesterol (HDL-c), triglycerides, and glucose were analyzed by the colorimetric method of dry chemistry and processed biochemically. Systolic blood pressure and diastolic blood pressure were measured using an automatic device. Body fat was estimated using a densitometry scanner. Results Adolescents who practiced sports were younger (p-value=0.001) and had a lower peak height velocity (p-value=0.001) than the non-sports group. The differences (Δ) after 12 months were of greater magnitude for the sports group when compared to the non-sports group (p-value=0.013), glucose (moderate magnitude in favor of the sports group; p-value=0.001), HDL-c (small magnitude in favor of the sports group; p-value=0.0015), and MetS (moderate magnitude in favor of the sports group; p-value=0.001). Conclusions The practice of sports in adolescents had a protective effect on the metabolic components of MetS.
Keywords: adolescent behavior; cardiovascular parameters; metabolic profile; risk factor; sport for development